Estudo da viabilidade técnica da utilização de vidro cominuido na produção de blocos de concreto para pavimentação - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Since the construction industry is responsible for generationg large volumes of solid waste, it places itself in a position of need in the search for sulutions to the environmental problems currently faced. In this line, the focus of the presente work takes into account the need to seek a suitable destination for waste from the more than one million tons of glass containers produced annually and, even if there is a possibility of recycling, this is not na economically viable option to municipalities away from large centers. Aiming the production of ecological pavers through the use of glass cominuído in diferente percentages of substitution the natural sand witch carries a high potencial or environmental impact, since de sand is a natural resource nonrenewable. The experimental program is divided into 3 major stages: collection (botles separation by color, washing, grinding and characterization of glass), the respective molding of the paver’s sample and, finally, the physical-mechanical control (dimensions, visual evaluation, compressive strength, abrasion resistence, water absorption, specifc mass and void index). Kidney aggregate substituions per glass were performed at percentages of 0, 10, 20 and 30% for de Amber color. At the control ages, the physical-mechanical characterization resulted in considerable improvements in all propertiesof the sample with 10% glass, reaching a 40 % increase in the compressive strength at 7 days. Moreover, the use of 20% of glass had similar properties, and even higher, reference samples.
Keywords: Engenharia civil; Vidro; Blocos de concreto; Pavimentação; Concreto seco; Civil engineering; Glass; Concrete blocks; Paving; Dry concrete; CNPQ::ENGENHARIAS